2011
DOI: 10.1542/pir.32-5-e53
|View full text |Cite
|
Sign up to set email alerts
|

The Preparticipation Sports Evaluation

Abstract: have disclosed no financial relationships relevant to this article. This commentary does not contain a discussion of an unapproved/ investigative use of a commercial product/device.Objectives After completing this article, readers should be able to:1. Perform a preparticipation history and physical examination and identify children and adolescents who may be at increased risk of morbidity or mortality from sports participation. 2. Recognize that many adolescents make infrequent contact with the medical system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It also serves as a chance to provide anticipatory guidance (31). Patients with T1DM should have a similar comprehensive pre-participation evaluation prior to initiation of any new physical activity.…”
Section: Pre-participation Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…It also serves as a chance to provide anticipatory guidance (31). Patients with T1DM should have a similar comprehensive pre-participation evaluation prior to initiation of any new physical activity.…”
Section: Pre-participation Evaluationmentioning
confidence: 99%
“…During periods of continuous physical activity, it is recommended that blood glucose levels be monitored about every 30 minutes, and then 15 minutes after completion of exercise, and at bedtime. In addition, more frequent monitoring may be needed over the next 24 hours due to increased risk of delayed hypoglycemia especially until the individual's glycemic response pattern to exercise is well defined (31,34). Optimal sports performance particularly in activities requiring the highest focus and precision would be expected when glycemic control is in a reasonably normal range as cognitive function and "mental efficiency" have been shown to be relatively lower during periods of hypoglycemia or significant hyperglycemia (35).…”
Section: Blood Glucose Monitoringmentioning
confidence: 99%
“…Specific health behaviors include targeted dietary modifications, increased levels of physical activity, decreased time in sedentary pursuits, and the elimination of exposure to tobacco smoke. 15 A meta-analysis of clinical trials in children and adolescents by Kelley and colleagues 16 found a 1% reduction in systolic blood pressure and 3% reduction in diastolic blood pressure with exercise interventions, although these findings were not statistically significant.…”
Section: Treatment Of Pediatric Hypertensionmentioning
confidence: 99%
“…However, athletes who have severe hypertension, characterized as greater than 5 mm Hg over the 99th percentile for age, sex, and height, should be disqualified from sports that require a high static demand, and should also avoid heavy weight training and powerlifting. 15 Patients with uncontrolled stage 2 hypertension should be restricted from participation in all competitive sports.…”
Section: Treatment Of Pediatric Hypertensionmentioning
confidence: 99%
“…Completion of a medical history and physical exam does not guarantee that individuals at risk for SCD will be identified (Peterson & Bernhardt, 2011; Seto, 2011). However, the AHA 12 elements are endorsed by the American Academy of Pediatrics (AAP), American Academy of Family Physicians (AAFP), and the American College of Sports Medicine (ACSM) (Peterson & Bernhardt, 2011) and are recommended for use in order to improve the standardization of physical examinations for athletes (Siddiqui & Patel, 2010). Routine use of electrocardiogram (ECG) to screen all competitive athletes is controversial and currently not recommended practice in the United States.…”
Section: Preparticipation Cardiovascular Screening Recommendationsmentioning
confidence: 99%